Characterization of older adults' sexual life in a health area - Juan Miguel Benítez García; Julio César Camero Machín; Jesús Cuello Ávila; Juan Carlos Curbelo Fajardo (Medisur)
Background: sexuality in the elderly is an essential factor in maintaining their quality of life. Objective: to characterize the sexual life of older adults in a health area. Methods: a descriptive and cross-sectional study was carried out in office 163 of the Raúl Sánchez University Polyclinic, in Pinar del Río in the period between September 2020 and September 2021. The universe of work was made up of 104 older adults and the sample consisted of 72 elderly, by means of intentional sampling by criteria. The instrument used was the interview; the data obtained were taken to a survey that with closed questions was personally applied to each of the study members. The following variables were analyzed: sex, marital status, education, sexual life, preferred sexual techniques, sexual functioning, causes that prevent the performance of the sexual act, associated diseases and drug use. Results: there was a predominance of primary school level, marital status without partners, female sex and sexual inactivity; vaginal intercourse predominated as the most frequent way of manifesting sexual activity. More than 90 % of men have some difficulty in sexual life. 22.5% present difficulties due to organic diseases. Conclusions: it is false that the elderly is an entity devoid of interest in sexual life, but it is affected by several factors, among which organic diseases and lack of a partner stand out.